Braunwald's heart disease : a textbook of cardiovascular medicine - Zipes, Douglas P.; Libby, Peter; Bonow, Robert O.; Mann, Douglas L.; Tomaselli, Gordon F.; Braunwald, Eugene, 1929- (Philadelphia, PA : Elsevier, 2019)
"Trusted by generations of cardiologists for the latest, most reliable guidance in the field, Braunwald's Heart Disease, 11th Edition, remains your #1 source of information on rapidly changing clinical science, clinical and translational research, and evidence-based medicine. This award-winning text has been completely updated, providing a superior multimedia reference for every aspect of this fast-changing field, including new material about almost every topic in cardiology"--Publisher's description
Part 1. Fundamentals of cariovascular disease -- Part 2. Molecular biology and genetics -- Part 3. Evaluation of the patient -- Part 4. Heart failure -- Part 5. Arrhythmias, sudden death, and syncope -- Part 6. Preventive cardiology -- Part 7. Atheroscerotic cardiovascular disease -- Part 8. Diseases of the heart, pericardium, and pulmonary vasculature bed -- Part 9. Cardiovascular disease in special populations -- Part 10. Cardiovascular disease and disorders of other organs
Includes bibliographical references and indexes
Keywords: Heart Diseases; Cardiovascular Diseases